Effect of surface modifications on the retention of cement-retained implant crowns under fatigue loads: An In vitro study - R Ajay; K Suma; Seyed Asharaf Ali; Jambai Sampath Kumar Sivakumar; V Rakshagan; V Devaki; K Divya (Wolters Kluwer Medknow Publications, 2017)
Background: Masticatory forces cause fatigue to the dental luting agents, adversely affecting the retention of these cement-retained crowns. Sandblasting (SB) and diamond abrading the abutment surface improves the bond strength of luting agents. However, the effect of acid etching (AE) on the implant abutment surface and the effect of other surface modifications under masticatory load are yet to be documented. Purpose: The aim of the study was to evaluate the effect of abutment surface modifications on the retention of cement-retained restorations subjected to cyclic fatigue loads. Materials and Methods: Forty Ni-Cr copings were made on Cp-titanium laboratory analogs. The specimens were divided into two groups as Group I: Uniaxial tensile loading (UTL) and Group II: Offaxial cyclic loading followed by uniaxial tensile loading [CTL]. Further subgrouped as, subgroup I: Control (C), subgroup II: SB, subgroup III: AE, and subgroup IV: SB + AE. The copings were luted with Zn2(PO4)3and subjected to uniaxial tensile loading. Copings were recemented, and CTL was conducted. Two-way analysis of variance was used as the statistical test of significance. Results: In relation to the subgroups, the bond strength of Zn2(PO4)3was higher in Group I than in Group II. The bond strength in subgroup IV was superior in both Group I and Group II (547.170 N ± 5.752 and 531.975 N ± 6.221 respectively). Conclusions: For both UTL and CTL, abutment SB + AE elicited maximum coping retention followed by AE. Off-axial cyclic loading adversely affected the retention irrespective of the surface modifications.